Implementasi Latihan Kemampuan Positif terhadap Harga Diri Rendah pada Klien dengan Gangguan Jiwa di UPT RSBL Pasuruan - Wulandari, Dwi; Widowati , Sri (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2025)
A 64-year-old male patient diagnosed with residual schizophrenia was admitted to the Bhakti Luhur Pasuruan Hospital for chronic low self-esteem. He exhibited withdrawn behavior, appeared depressed, lacked self-confidence, described himself as worthless, and was unable to care for himself. He also had a history of traumatic experiences and discriminatory treatment from his environment, which led to a decline in self-concept and motivation for activities. The intervention provided consisted of five days of positive skills training, which included building trusting relationships, recognizing remaining abilities, expressing positive feelings, and strengthening adaptive behavior through praise and support. After the intervention, the patient showed positive changes in the form of improved communication, appeared more confident, began to be active in simple activities, was able to articulate his abilities, and performed self-care independently. These results indicate that positive skills training is effective in improving self-esteem and adaptive functioning in patients with residual schizophrenia, so it can be used as a sustainable nursing intervention in psychosocial rehabilitation.